Fostering political leadership for the demographic dividend in Africa: relevant cultural values. Issue 5 (4th July 2018) - Izugbara, Chimaraoke O.; Tilahun, Tizta; Owii, Hilda
ABSTRACT: A foremost challenge to the realisation of the accelerated economic growth of the demographic dividend in Africa remains the commitment of the region's political leadership to creating the enabling contexts to maximise the potential of its youthful population. This viewpoint considers three critical African cultural mores – the reverence-for-posterity norm; leader-as-community-proxy culture; and the elder tradition – that offer unique levers for fostering political leadership for the demographic dividend in Africa. Strategies for successfully tapping these cultural traditions require further research.